Klassifikation von Gliomen: Aktuelle Fortschritte und Perspektiven = Classification of gliomas : current progress and perspectives - Capper, David; Reifenberger, Guido (Der Nervenarzt, 2015)
SummaryThe diagnostic subdivision of gliomas is traditionally based on histological features as defined by the World Health Organization (WHO) classification of tumors of the central nervous system. In recent years molecular studies have identified a number of genetic and epigenetic markers that could contribute to an improved tumor classification and better prediction of response to therapy and prognosis in the individual patient. The most important molecular tests with differential diagnostic relevance in patients with astrocytic and oligodendroglial tumors include the detection of genetic mutations in the isocitrate dehydrogenase 1 (IDH1), IDH2, alpha thalassemia/mental retardation syndrome X-linked (ATRX), histone H3.3 (H3F3A) and v-raf murine sarcoma viral oncogene homolog B (BRAF) genes as well as the demonstration of codeletions of chromosomal arms 1p and 19q. Important predictive markers that have been linked to the response to alkylating chemotherapy are O-6-methylguanine-DNA methyltransferase (MGMT) promoter methylation in glioblastoma patients and 1p/19q codel status in anaplastic glioma patients. Oncogenic c11orf95/RELA fusion gene formation is characteristic for a subgroup of patients with supratentorial ependymoma. In addition to diagnostic testing of individual genes, novel microarray and next generation sequencing (NGS) techniques show promising perspectives in glioma diagnostics. The assessment of DNA methylation profiles using DNA methylation arrays representing 450,000 CpG dinucleotides distributed throughout the human genome (450 k array test) now allows the robust molecular classification of gliomas into clinically relevant entities and variants. Moreover, glioma-associated gene panel NGS promises the timely parallel sequencing of relevant diagnostic and predictive marker genes in a single test. It will now be a major task to integrate these novel results and techniques into the conventional histological procedures in the up-coming revision of the WHO classification.
Gesehen am 25.04.2017